Tanaidacea (Crustacea) from Macaronesia II. The deep-water fauna from the Azores archipelago, Portugal - Larsen, Kim (Zootaxa, 2012)
As part of Portugal’s bid for extending the country’s exclusive economic zone, the EMEPC collection program wasinitiated. From this program several new species of Tanaidacea have been collected during various expeditions. In thispaper three new species of Tanaidacea are described from the Azores archipelago in the Mid-Atlantic, Portugal. Two ofthem belong to the apseudomorphan genera Leviapseudes (L. macaronesia), Pseudosphyrapus (P. azorensis), and another new species belong to the tanaidomorphan genus Paratanais (P. pseudomartinsi).